2020
DOI: 10.1088/1742-6596/1515/5/052016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of micromechanical properties of fused alumina and silicone carbide grains

Abstract: Micromechanical properties of abrasive material grains of fused alumina and silicone carbide are investigated applying the microindentation method. Such parameters as microhardness, microbrittleness, and microstrength were evaluated depending on the penetration depth of the Vickers diamond pyramid to the 0.5 — 5.0 µm thick surface under analysis. The microhardness parameter is the stress required for formation of a brittle failure area within the pyramid imprint. The microbrittleness criterion defines the rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Cr-Ti fused alumina (samples 4, 5, and 6) after high-temperature heating behaves variously, depending on the Ti 3+ content in the solid solution: the structure of brown grains (the ratio in the TiO2/Cr2O3 solid solution ≥ 1.5) becomes more balanced; as for purple grains (TiO2/Cr2O3 ≤ 1.5), defects are distributed non-uniformly, so the structure remains unbalanced similarly to Cr alumina. The study revealed higher values of Cr-Ti fused alumina micromechanical parameters [4,7,8,9], besides, purple grains have the maximum values; such Cr-Ti fused alumina reaches the maximum values of micro hardness and crack resistance after heat treatment at 1250 °C.…”
Section: Study Resultsmentioning
confidence: 97%
“…Cr-Ti fused alumina (samples 4, 5, and 6) after high-temperature heating behaves variously, depending on the Ti 3+ content in the solid solution: the structure of brown grains (the ratio in the TiO2/Cr2O3 solid solution ≥ 1.5) becomes more balanced; as for purple grains (TiO2/Cr2O3 ≤ 1.5), defects are distributed non-uniformly, so the structure remains unbalanced similarly to Cr alumina. The study revealed higher values of Cr-Ti fused alumina micromechanical parameters [4,7,8,9], besides, purple grains have the maximum values; such Cr-Ti fused alumina reaches the maximum values of micro hardness and crack resistance after heat treatment at 1250 °C.…”
Section: Study Resultsmentioning
confidence: 97%